Helium-Hydrogen Synergistic Effects in Structural Materials Under Fusion Neutron Irradiation - Huang, Jia; Liu, Haocheng; Gao, Zhiying; Su, Yue; Liu, Qingyuan; Ge, Wei; Luo, Fengping; Xia, Songqin; Cao, Liuxuan; Xue, Jianming; Wang, Yugang; Wang, Chenxu (Frontiers in Materials, 2022)
In fusion reactors, 14 MeV high-energy neutron irradiation of structural materials will produce large amounts of helium and hydrogen simultaneously with displacement defects. These He and H atoms will interact with displacement defects, leading to He-H synergistic effects and aggravating the irradiation damage. Currently, there exist no available high-flux fusion neutron sources. Additionally, the neutron energy spectrum and the generation of He and H in fission reactors or spallation neutron sources greatly differ from those in fusion reactors. Multi-ion beam irradiation is a promising method to emulate the synergistic effects induced by fusion neutron irradiation. This review summarizes the experimental studies on the He-H synergistic effects, and analyzes the effects of He and H on cavity evolution and swelling under multi-ion beam irradiation. The roles of various experimental factors are also discussed. More systematically controlled experiments are suggested to develop a comprehensive understanding of He-H synergistic effects in structural materials.